Customer Acceptance of IPTV After Service Failure - Yi-Ning Katherine Chen (International Telecommunications Society (ITS), 2018)
As a case study of the 2017 contract breach crisis involving Chunghwa Telecom (CHT) and its IPTV service, MOD, this study inspects the synergistic influences among perceived service quality, acceptance of technology, trust, satisfaction, and consumers' post-crisis repurchase intentions. With 546 participants randomly surveyed online, our findings demonstrate that among all the factors, only satisfaction and acceptance have significantly positive bearing on post-crisis repurchase intentions. Second, albeit extraneous to the repurchase intentions, perceived service quality has strong direct association with consumers' acceptance of MOD. Third, the contract breach crisis deteriorated rapidly due to administrative rather than technical disappointments. Overall, to quickly augment the repurchase intentions, CHT is advised to lift users' acceptance through sophisticating perceived customization and usefulness. To sustain repurchase intentions, meliorating service quality is the next step. Finally, to overcome the contract breach crisis, CHT needs both consistent and just compensation policies.
Keywords: 330; IPTV; MOD; service quality; TAM; trust